An Analysis of Student Satisfaction with Student Services in the Industrial Engineering Department of Universitas Pamulang - Khairunnisa, Khairunnisa; Arini, Dewi Ulfah; Khairunisa, Meutia Dwina (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
Student satisfaction is a key indicator of the quality of higher education services. In the context of the Industrial Engineering Department at Universitas Pamulang, student satisfaction with student services plays a critical role in supporting academic success and student well-being. This study aims to analyze the level of student satisfaction with the services provided by the department. A quantitative descriptive research method was employed, with a sample of 100 students selected through simple random sampling. Data was collected using questionnaires and analyzed through descriptive statistical analysis to assess perceptions of service quality. The results showed that reliability was the most significant factor, contributing 22.4% of the total variance in satisfaction, followed by assurance and empathy (20.3%) and responsiveness (18.9%). Interview data revealed that responsiveness, particularly in handling student complaints, was perceived as lacking, which negatively affected overall satisfaction. These findings suggest the need for targeted improvements in responsiveness, empathy, and reliability to enhance the quality of student services. Improving these aspects can lead to better student experiences and strengthen the department’s academic support system.